Transformasi Peran Mekah dalam Dinamika Kebudayaan Islam di Nusantara: Studi Komperatif - Rifai, Ahmad; Abdillah, Irhamni Sabil; Fahmi, Faiz Fikri Al; Arum, Aqilatun; Nasuha, Siti Alifah Ailatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research uses a historical and comparative approach to determine changes in the role of Mecca in the dynamics of Islamic culture in the archipelago. Mecca, the holy city of Muslims, is not only a spiritual center and symbol of unity, but also plays a strategic role in spreading Islamic values and is popular in various parts of the world, including the archipelago in the formation of Islamic cultural identity. This study focuses on the mechanisms for the spread of Islam through various channels such as trade, bi al-har da'wah, marriage, education, and cultural acculturation which allows Islam to be widely accepted in the archipelago without any coercion. In addition, theories regarding the origins of the Islamic invasion of Indonesia, such as the Meccan, Gujarati, Persian and Chinese theories, are evaluated to understand the diversity of origins and processes of Islamization. The important role of Islamic scholars and kingdoms such as the Sultanate of Demak, Cirebon, and Banten in strengthening the spread of Islam in the region is also analyzed. This research shows that Mecca as the center of Islamic civilization has a significant influence on religious practices in the archipelago and the formation of the character of local Islamic culture, including the direction of worship centered on the Kaaba. The results of this research show that although the role of Mecca in the dynamics of Islamic culture in the archipelago continues to change, the universal Islamic values of Mecca remain relevant in responding to current challenges and in various Islamic cultures guarantee continuity cultural diversity of the archipelago.